Findbuch des Bestandes Abt. 47: Christian-Albrechts-Universität Kiel, Teil 1: 1665-1945 - Asmussen, Georg (Veröffentlichungen des Landesarchivs Schleswig-Holstein, 2007)
The archive of the University of Kiel was initially established at the University of Kiel itself and has alreday been organized there in the past. A first list of the files exists for the year 1748. In 1934 a depositary contract was concluded with the prior State Archive in Kiel. In the summer of 1934, the first university records were handed over . These files still form the core of university tradition for the period before 1945. Since most of the old files and the current registry had been burned during the Second World War, new files had to be created from 1945 onwards and their archivability had to be awaited. Between 1964 and 1998, several large and small file donations came from the university to the State Archives at irregular intervals. As a result of an agreement concluded in 2002 between the University and the State Archives of Schleswig-Holstein, further files were added to the archive's holdings.